PENGARUH KUALITAS PRODUK DAN KEPERCAYAAN TERHADAP LOYALITAS PELANGGAN PADA PT TRIO ESTRO CASUAR DI KOTA BATAM - Julianto, Leonard; Nainggolan, Nora Pitri (LPPM Universitas Putera Batam, 2021)
This research is intended to analyze the effect of product quality and trust on customer loyalty at PT Trio Estro Casuar. The method of analysis used in this research is quantitative analysis and obtaining data through questionnaires. The population in this study were customers of PT Trio Estro Casuar, of which 125 customers. The sampling technique used is the Non Probability sampling technique which uses saturated sampling with a sample of 125 customers of PT Trio Estro Casuar. Furthermore, the collected data were analyzed using multiple linear regression analysis and hypothesis testing to determine the effect of product quality and trust on customer loyalty at PT Trio Estro Casuar with the help of the SPSS (Statistical Package for the Social Sciences) calculation tool version 25. The results of this study indicate that Product quality and trust have a positive and significant effect on customer loyalty at PT Trio Estro Casuar. Product quality variable partially has a positive and significant effect on the customer loyalty variable and the trust variable partially has a positive and significant effect on the customer loyalty variable. Simultaneously, product quality and trust have a positive and significant effect on customer loyalty at PT Trio Estro Casuar.